Acceleration of Subwavelength Polaritons by Engineering Dielectric-Metallic Substrates - Feres, Flávio H.; Feres, Flávio H. [UNESP]; Mayer, Rafael A.; Barcelos, Ingrid D.; Freitas, Raul O.; Maia, Francisco C. B. (American Chemical Society (ACS), 2020)
By synchrotron infrared nanospectroscopy, we demonstrate modulation of momentum and group velocity of subdiffractional hyperbolic phonon-polaritons (HP2), in hexagonal boron nitride nanocrystals, by varying the SiO2 film thickness in the hBN/SiO2/Au heterostructure. We reveal acceleration of the HP2 pulse in a hBN/(SiO2 wedge)/Au heterostructure with gradient of the SiO2 thickness. The acceleration is explained by a semiclassical modeling considering the polariton pulse as a free quantum particle with effective mass dependent on its group velocity. In quantitative agreement with simulations and semiempirical analysis, the modeling predicts an average acceleration of 1.5 × 1018 m·s-2 close to that of ∼1.45 × 1018 m·s-2 obtained from experimental inputs. From the fundamental aspect, the polariton acceleration allows discussing the undulatory-corpuscular behavior of polariton quasi-particles. The acceleration induced by the wedge is a general effect that can provide for control of the polariton pulse dynamics, which is compelling for future polaritonic devices.
Keywords: group velocity modulation; polariton acceleration; polariton momentum-tuning; polariton wave-particle behavior; substrate engineering; subwavelength polariton